2022
DOI: 10.17221/110/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> emissions in a soil under different tillage practices

Abstract: CO2 emissions represent one of the greenhouse gases significantly affecting climate change. Reduced tillage practices can contribute to the mitigation of CO2 emissions from soils. The effect of tillage practices with different straw incorporation on CO2 emissions was studied in field experiments in the years 2020 and 2021. The winter wheat straw was used in 2020, and spring barley straw in 2021. Treatments were: (1) chiselling to 10–12 cm; (2) shallow chiselling (5–6 cm depth); (3) straw mulch, and (4) stubble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…8). Similar results were obtained by Mühlbachová et al (2022), who achieved an increase in value up to 1.7-fold. In areas with scarce rainfall, soil conservation technologies are vital, as other types of technology cause soil desertification (Ruan et al, 2021).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…8). Similar results were obtained by Mühlbachová et al (2022), who achieved an increase in value up to 1.7-fold. In areas with scarce rainfall, soil conservation technologies are vital, as other types of technology cause soil desertification (Ruan et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…Soil characteristics were as follows: medium They are often produced in V-shaped blades with an operating width of 46 cm or more (Rédl and Findura, 2021). Furthermore, Mühlbachová et al (2022) observed that tillage practices and varying construction of the devices employed have an impact on CO 2 emissions as well.…”
mentioning
confidence: 99%
“…For the FM variant, the CO 2 emissions coming from diesel combustion are therefore 5.12 kg ha −1 lower. Although the reduction in CO 2 emissions can be ensured by reduced tillage [41], it is necessary to address this issue also in the case of conventional technology. CO 2 emissions in agriculture, however, are a very complex issue that needs to be considered in a broad ecosystem cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of soil aggregates potentially leads to elevated soil aeration, greater soil temperatures, and reduced soil moisture, resulting in increased CO 2 fluxes. Other studies have also confirmed that, aside from tillage depth, soil temperature, and moisture, the incorporation of crop residues could potentially be decisive for increased CO 2 emissions from soil [34]. The lower bulk density witnessed in the ploughed treatments enhanced the CO 2 emissions in the soil, contrary to the suppression of CO 2 in higher bulk density, which is synonymous with no tillage.…”
Section: Soil Ghg Emissionsmentioning
confidence: 90%